Where PPE went wrong: Oakeshott's liberal learning, language, and the university. Issue 3 (December 2014) - Norman, Jesse
<x xml:space="preserve">Abstract</x> Jesse Norman Applies 20th‐century philosopher Michael Oakeshott's ideas about culture, learning and experience to explore contemporary attacks on the political ranks of 'college‐educated' PPE‐ites.